Phytochemical Screening and Formulation of Hand Sanitizer Gel Preparations from Temu Hitam Rhizome Extract (Curcuma aeruginosa Roxb) - Sari, Rika Puspita; Efa Harnis, Zola; Irmayanti Harahap, Nina (Publisher Cv. Inara, 2022)
Temu Hitam (Curcuma aeruginosa Roxb) is one of the most widely grown plants in Indonesia at an altitude of 400–750 m asl and contains many secondary metabolites, including flavonoids, alkaloids, saponins, tannins, and curcuminoids, which in the test had antibacterial activity and growth inhibitors. worm larvae in the gastrointestinal tract and the effect of increasing the body's immunity The purpose of this study was to identify the content of secondary metabolites contained in the rhizome of black turmeric, which would then be formulated into gel hand sanitizer preparations. Secondary metabolite testing was conducted on alkaloids, flavonoids, saponins, tannins, steroids/triterpenoids, and glycosides. Three different hand sanitizer gel formulations were created using different extract concentrations, 5%, 10%, and 15%. Evaluation tests were then run on the preparations, including stability, organoleptic, homogeneity, pH, and dispersion tests. Alkaloids, flavonoids, tannins, saponins, and steroids were found in the temu hitam rhizome, according to the results of secondary metabolite testing. The dosage form was semi-solid, had a light brown to blackish brown hue, a distinct spice scent, was homogeneously prepared, and had a pH of 7.0, according to the examination of the formulation results 4,1 ± 0,17; 4,4 ± 0,19; 4,9 ± 0,08; 4,9 ± 0,09, viscosity 2378 ± 209,9; 3340 ± 220,7; 4509 ± 285,6; 4881 ± 276,7; and spreadability test 5; 6,2; 5,4; 4,9 cm . The conclusion of this study is that the results of the phytochemical screening of simplicia and the ethanolic extract of the Temu Hitam rhizome showed positive results, containing secondary metabolites of alkaloids, flavonoids, tannins, saponins, glycosides, and steroids/triterpenoids that can be formulated into hand sanitizer gel preparations that meet the requirements for preparation evaluation.